Situation of Landless Madheshi Dalit: A Case Study of Lalparsa VDC of Parsa District - Tiwari, Sushma (International Journal of Social Sciences and Management, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE NE MicrosoftInternetExplorer4 <![endif]–> In Madhes/Terai, the degree of social voice of the Terai Dalit is less pronounced in spite of the degree of exploitation and deprivation. In particular, landlessness in an agrarian society is more related to agrarian capitalism i.e. the most of the land is concentrated on the hands of few for their own economic interest, and the rest majority of the people are landless. The study aims to examine the situation of landless Madheshi Dalits and their actual problem faced by these landless Dalits. The study has selected Lalparsa VDC of Parsa District for field survey and both qualitative and quantitative techniques have used to get information from this group. The article based on the research, shows that most of the land is concentrated on the hands of few for their own economic interest, and the rest majority of the people are landless. Dalit are disadvantaged group in term of land ownership and also in economical and social dimensions. Most of the Madheshi Dalits are landless and household living in ailani (Government land with no legal tender) land. They have no access to land resources and have been suffering from landlessness, poverty and poor socio-economic condition in the country and situation is worst among Madheshi Dalits. DOI: http://dx.doi.org/10.3126/ijssm.v1i1.8689 Int. J. Soc. Sci. Manage. Vol.1(1) 2014 51-57 <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; mso-bidi-font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:Mangal; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –>